Cervical Thymic Cyst in an Adult - Hassan A. Alzahrani; Javeria M. Iqbal; Amani K. Abu Shaheen; Bandar N. Al Harthi (Case Reports in Surgery)
Cervical thymic cysts (CTCs) are unusual lesions, representing only 1% of cystic cervical masses. Diagnosis of this condition in adults is even rarer. We report a 34-year-old female who presented with asymptomatic progressively growing left-sided neck swelling. Neck ultrasound (US) showed a large cystic lesion with septation, compressing the ipsilateral vessels. Magnetic resonance imaging (MRI) confirmed the US findings. Surgical excision was performed which subsequently showed findings consistent with CTC. CTC in adult is extremely rare, with few reported cases identified in the literature. Thymic gland anomalies in the neck are the consequences of an arrest in the descent of the gland, sequestration of the thymic tissue, or failure of involution. The diagnosis of this condition is rarely done prior to surgical excision. The clinical presentation, radiologic imaging, surgical findings, and histologic appearance are all essential components to make the correct diagnosis of this very rare differential diagnosis of cystic lateral neck swelling.